Coating anode prepared by plasma sintering and preparation method thereof
The preparation of coated titanium anode through plasma sintering technology solves the problems of slow temperature rise and poor temperature uniformity in traditional methods, achieving a more stable crystallization structure and a higher service life.
Patent Information
- Application Number
- CN202411546246.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-18
Smart Images

Figure CN119465313A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytic anodes, and in particular relates to a coated anode prepared by plasma sintering and a preparation method thereof. Background Art
[0002] Since the birth of coated titanium anode, the industry has been widely used in hydrometallurgy and electrolytic production. Since the electrolytes in these industries are strongly acidic and alkaline, there is a high demand for corrosion resistance, low potential and high selectivity of electrode materials.
[0003] However, with the increasing popularity of industrial applications and the gradual improvement of industrial standards, the working environment of the anode has become more severe, which may lead to the peeling of the precious metal coating, and then cause the anode failure and lead to the loss of precious metals, causing economic losses to the company.
[0004] The preparation method of coated titanium anode is usually thermal decomposition method, and the production equipment is basically a resistance box furnace, which has the disadvantages of slow heating and poor temperature uniformity. The coating needs to be kept at a specific temperature for a certain period of time, and before that, a lot of heating time is required to reach the specified temperature. This process will affect the nucleation and growth time of the coating crystals.
[0005] Plasma sintering is a new sintering method. It heats the conductive metal through the plasma generated by pulse current, so that the metal reaches the specified temperature in a short time. It has the distinctive characteristics of fast heating speed, short sintering time, energy saving and environmental protection. Through plasma sintering coating, the heating time is significantly shortened and the temperature uniformity is also significantly improved, which can effectively improve the crystal morphology of the coating and improve the performance and life of the anode material.
[0006] Existing plasma sintering has advantages such as fast heating rate and uniform temperature, but it requires connecting both ends of the anode to power and applying a pulse current. Therefore, there are still many equipment problems that need to be overcome to achieve industrial production.
[0007] The existing plasma sintering technology is mainly used for the preparation of bulk metal or ceramics, which mainly makes the temperature of metal or ceramic powder rise rapidly to close to the melting point, and dissolves into bulk products under a certain pressure. It is also used in material connection and gradient material preparation, mainly using pulse discharge heating and pressurization to form dense metal or ceramics. This process mainly uses the principle of fast plasma heating speed and does not require pressurization, so it is easier to implement in equipment design than traditional plasma sintering.
[0008] In response to the above-mentioned problems of coated titanium anodes, the present invention proposes a coated titanium anode prepared by plasma sintering, which has a stable crystalline structure, maintains high active sites while improving structural stability, reduces the production cost of the coated titanium anode, and increases service life. Summary of the invention
[0009] In response to the above-mentioned coated titanium anode problem, one of the objectives of the present invention is to provide a coated titanium anode prepared by plasma sintering, which has a stable crystalline structure, maintains high active sites while improving structural stability, reduces the production cost of the coated titanium anode, and increases service life.
[0010] To achieve the above technical objectives, the technical solution of the present invention is implemented as follows:
[0011] In a first aspect, the present invention provides a coated anode prepared by plasma sintering, comprising a metal substrate and a metal activation layer coated on the surface of the substrate, wherein an oxide intermediate layer is provided between the substrate and the metal activation layer;
[0012] The metal activation layer is composed of at least one oxide selected from Ta, Pt, Pd, Rh, Ru, Ir, and Os, which can effectively catalyze the electrochemical process, effectively reduce the overpotential, and has a slow anode corrosion rate and good stability;
[0013] The oxide intermediate layer is composed of at least one oxide selected from Ti, Ta, Nb, Pt, Pd, Rh, Ru, Ir, and Os. The intermediate layer protects the substrate and connects the metal activation layer. It plays a transitional role in effectively combining the substrate and the metal activation layer. Its composition is generally composed of one or more components of the substrate and the metal activation layer.
[0014] The oxide intermediate layer and the metal activation layer are both made by plasma sintering.
[0015] The coated anode made by plasma sintering has a lower operating potential and a longer life, which shows that plasma sintering can effectively improve the overall catalytic activity and stability of active metals.
[0016] Compared with the existing sintering furnace, the biggest difference of the plasma sintering in the present application is the faster heating rate. The faster the heating rate, the faster the heating rate. The coating composition is generally the oxide of mixed metals, and the oxidation temperature range of different metals is different. The heating time is too long will cause the metal with low oxidation temperature to oxidize prematurely, thereby affecting the solid solution of the mixed metal and causing the formation of branched segregation crystals, affecting the overall performance and service life of the coating; shortening the heating time, so that the temperature rises rapidly to the specified temperature, allowing the mixed metal to crystallize at the same time, improving the solid solubility and crystallization uniformity of the two, forming a firm columnar crystal, and improving the service life.
[0017] In some achievable methods of the first aspect, the oxide intermediate layer precursor solution is prepared by evenly mixing solutions containing components A1 and B1 and dissolving them in an organic solvent or hydrochloric acid; wherein components A1 and B1 are at least one of Ti, Ta, Nb, Pt, Pd, Rh, Ru, Ir, and Os.
[0018] The organic solvent here is generally various alcohol solvents, such as isopropanol and n-butanol.
[0019] In some implementable embodiments of the first aspect, the thickness of the oxide intermediate layer is 0.1 to 1 μm.
[0020] In some achievable methods of the first aspect, the active metal layer precursor solution is prepared by uniformly mixing solutions containing components A2 and B2 and dissolving them in an organic solvent or hydrochloric acid;
[0021] The components A2 and B2 are at least one metal selected from Ta, Pt, Pd, Rh, Ru, Ir, and Os.
[0022] In some implementable embodiments of the first aspect, the thickness of the metal activation layer is 1 to 20 μm.
[0023] Since the metal activation layer is a porous structure, its thickness will affect the actual catalytic effect. The thicker the thickness, the better the catalytic effect. However, the thicker the porous structure, the worse its bonding strength, which will cause the precious metal activation layer to fall off quickly, increasing the cost of use.
[0024] In some achievable methods of the first aspect, the substrate is a valve-type metal selected from titanium, tantalum or niobium, and forms a dense oxide film at an oxidation potential without dissolving;
[0025] And / or, the valve-type metal is in the form of a plate, a mesh or a tube.
[0026] In a second aspect, the present invention provides a method for preparing a coated anode prepared by plasma sintering, which is used to prepare the above-mentioned coated anode, and the preparation method comprises the following steps:
[0027] (1) Surface roughness treatment: The cut substrate is treated with sandblasting, shot blasting or magnetron sputtering to give the substrate a certain degree of roughness. Increasing the surface roughness of the substrate can effectively increase the specific surface area of the anode, thereby increasing the surface active area and improving the activation ability of the anode. Increasing the roughness will also improve the coating adhesion to a certain extent and increase the service life of the anode.
[0028] (2) Surface activation treatment: Use alkaline washing and degreasing or acid washing as pretreatment to remove oxides on the surface of the substrate, and then dry it for use. The purpose of surface activation treatment is to remove the oxide layer produced by processes such as sandblasting, and to improve the bonding strength and conductivity of the base layer and the activation layer.
[0029] The pickling can be carried out by using one or more mixed acids such as hydrofluoric acid, sulfuric acid, oxalic acid, nitric acid and hydrochloric acid.
[0030] (3) Preparation of the intermediate layer: uniformly coating the oxide intermediate layer precursor solution on the surface of the substrate, cooling to room temperature after plasma sintering to obtain an oxide intermediate layer supported on the surface of the substrate, and obtaining a semi-finished product having an oxide intermediate layer.
[0031] (4) Preparation of metal activation layer: The active metal layer precursor solution is evenly coated on the surface of the semi-finished product, and the metal activation layer is prepared by plasma sintering to ensure that the coated anode surface has abundant catalytic active sites and a stable structure.
[0032] Specifically, the coating process can be one or more combinations of rolling, spraying, dipping and sputtering. The coating amount of the metal activation layer represents the amount of the metal activation layer, which directly affects the activation ability of the anode and the use effect of the client.
[0033] In the present application, plasma sintering is to oxidize a salt solution containing precious metals into precious metal oxides with conductive activity, and the growth morphology of the crystals will affect the activation ability and service life of the anode.
[0034] Since the intermediate layer and the catalytic layer are coated and sintered layer by layer, the use of plasma sintering can reduce the sintering time, which will greatly reduce the cracks caused by high-temperature sintering, reduce the substrate passivation caused by high-temperature sintering and cracks, and improve the overall performance of the coated anode.
[0035] In some achievable embodiments of the second aspect, during the plasma sintering process of step (3) and step (4), oxygen or air is introduced to oxidize the metal salt.
[0036] Conventional plasma sintering equipment is generally used for the preparation of bulk metals, and its steps include powder grinding - placing in a mold - compacting - placing in the plasma sintering equipment furnace chamber - vacuuming - pressurizing - energizing sintering - cooling and other processes. In order to improve the compactness of bulk metals and prevent oxidation of powder raw materials, it is necessary to pressurize and evacuate the furnace chamber. The coating anode involved in the present invention is essentially to oxidize precious metal salts into precious metal oxides by thermal decomposition. The substrate itself is a dense bulk metal, so no pressurization is required; and the coating preparation process requires an oxygen environment for oxidation reaction, so there is no need to evacuate, but instead it is necessary to introduce excess air or oxygen atmosphere into the furnace chamber.
[0037] Therefore, compared with conventional plasma sintering, the plasma sintering step in the present application has different requirements for the ambient atmosphere and vacuum degree, but these are parameters that can be controlled by the equipment, so there is no need to modify the equipment.
[0038] In some achievable embodiments of the second aspect, the plasma sintering comprises the following steps:
[0039] The two ends of the anode are connected to the positive and negative electrodes of the plasma respectively, and heating begins after power is turned on. The heating rate in the plasma sintering device is 80-120℃ / min, and the anode is heated from room temperature to 300℃-550℃. At this temperature, a dense oxide layer will form in the middle layer, which will protect the substrate from corrosion and oxidation, and connect the metal activation layer to increase the bonding force; the metal activation layer will be oxidized into a precious metal oxide crystal structure at this temperature, which will provide electrocatalytic activity.
[0040] The traditional sintering method is to radiate the material surface through resistance heating, while the plasma sintering in the present invention is to directly heat the metal by passing a pulse current, so the anode here refers to the semi-finished anode coated with the precursor coating liquid. The parameters of the pulse current correspond to the set sintering temperature, so only the required sintering temperature needs to be set, and there is no need to set the relevant parameters of the pulse current.
[0041] During the sintering process, excessive air or oxygen atmosphere is introduced, and the temperature is kept at normal pressure for 5min to 20min. After sintering, it is placed in the air to cool to room temperature. Sintering is the process of crystal nucleation and growth. The sintering time should not be too short or too long. Too short will lead to incomplete oxidation of precious metal salts and too little crystallization. Too long will lead to excessive crystal growth, which will affect the anode bonding strength and overall life.
[0042] Since both the intermediate layer and the activation layer are oxidation processes of metal salts and the types of salts are similar in the same system, there is no obvious change in the main steps and temperature parameters.
[0043] Compared with existing sintering furnaces, plasma heating generates heat energy by applying pulse current to the metal, causing the metal to heat up rapidly. It has the characteristics of uniform heating, fast heating speed, short time, high production efficiency and uniform grain growth.
[0044] The composition of the metal activation layer is generally a mixed metal oxide. Taking the iridium-tantalum coating as an example, the oxidation temperature of iridium is 300-550℃, and the oxidation temperature of tantalum is above 500℃. If the heating time is too long, the iridium will crystallize prematurely, affecting the solid solution of the two, and causing the formation of branched segregation crystals, affecting the overall performance and service life of the coating. If plasma sintering is used to shorten the heating time, the temperature is quickly raised to above 500℃, and the two are crystallized at the same time, the solid solubility and crystallization uniformity of the two can be significantly improved, forming a firm columnar crystal, and prolonging the service life of the coating anode.
[0045] During the pretreatment of the coated anode, sandblasting or magnetron sputtering is usually added to increase the roughness of the substrate surface; acid etching is also used to remove the surface oxide layer and activate the substrate surface so that the substrate and the intermediate layer are effectively combined together. The intermediate layer itself is a transition layer that connects the substrate and the coating. The quality of the connection between the coating and the substrate is closely related to the ratio and concentration of the intermediate layer, and there will be corresponding differences depending on the actual substrate and coating used.
[0046] In addition to the pretreatment of the substrate, the most important process is the coating and sintering process. The main reasons that affect the uniformity of the coating are the dispersion of the precursor solution and the uniformity of the precursor solution applied to the surface. The anode substrate is a dense metal material. Unlike traditional plasma sintering materials, the porosity is too large to affect the overall physical properties of the material. The coating is prepared layer by layer and the surface is crystallized. The purpose is to prepare a porous structure (such as the crack morphology in the SEM image). Because the coated anode is mainly used in electrocatalysis in various fields, the porous and crystalline structure can effectively increase the catalytic active area of the coating, thereby improving the catalytic ability of the coating. Excessive crystal growth of the coating will deteriorate the crystal strength and reduce the ability to resist environmental impact; the increase in porosity will affect the protection of the coating and the intermediate layer to the substrate, which can easily lead to substrate passivation failure, thereby affecting the overall life of the anode.
[0047] The factors that affect the pore and crystal size are the overall time of the sintering stage and the holding time to reach the specified temperature. The holding time will affect the crystal growth. If the holding time is too long, it will cause excessive crystal growth, increase the active area but make the crystal brittle, thus affecting the overall service life. If the heating time is too long, a large amount of thermal stress will accumulate inside the metal, causing serious surface cracking, increasing the crack width on the substrate surface and the porosity of the coating, increasing the probability of substrate erosion, and affecting the overall life of the coating.
[0048] The method of controlling the holding time is relatively simple. Using a timer or setting a heating program to end the heating within a fixed time after reaching the specified temperature can achieve the desired effect. The shortening of the heating time depends on the power limit of the equipment. Heating the furnace cavity with a resistance wire and heating the plate surface with heat radiation has great limitations. The fastest plasma sintering can reach 500-800℃ / min. The faster heating rate will generate internal stress in a short time, forming short and shallow cracks on the coating surface (such as Figure 2 a), improving the catalytic efficiency of the coating.
[0049] Plasma sintering, with its faster heating rate, significantly shortens the heating time, thereby effectively improving the surface and crystal morphology of the coating, which is undoubtedly its outstanding advantage.
[0050] In a third aspect, the present invention provides an application of a coated anode prepared by plasma sintering, and the coated anode prepared by plasma sintering is used in the fields of copper foil production, electrolytic chlorine production, water treatment, seawater desalination, and printed circuit board manufacturing.
[0051] As a sixth solution to the above problems, the present invention provides a coated titanium anode prepared by plasma sintering, which includes a conductive valve-type metal and a dense intermediate layer formed by plasma sintering on a metal substrate, and a surface activation layer of a precious metal or a non-precious metal. The manufacturing process includes substrate cutting, surface roughening, activation treatment for removing an oxide layer, intermediate layer coating and plasma sintering, surface activation layer coating and plasma sintering, ensuring that the surface has abundant catalytic active sites and a stable structure.
[0052] Effects of the Invention
[0053] 1. The present invention adopts valve-type metal substrates through size cutting, substrate pretreatment, preparation of intermediate layers and activation layers, and plasma sintering. Its characteristics are that compared with the coating anode sintered in a conventional resistance furnace, it has a lower use potential and a longer life. This shows that plasma sintering can effectively improve the overall catalytic activity and stability of active metals.
[0054] 2. Compared with the existing sintering furnace, the biggest difference between plasma sintering and the existing sintering furnace is that the heating rate is faster than that of the existing sintering furnace. The coating composition is generally a mixed metal oxide, and the oxidation temperature range of different metals is different. If the heating time is too long, the metal with low oxidation temperature will oxidize prematurely, thereby affecting the solid solution of the mixed metal and causing the formation of branched segregation crystals, affecting the overall performance and service life of the coating; shortening the heating time, so that the temperature rises rapidly to the specified temperature, allowing the mixed metal to crystallize at the same time, improving the solid solubility and crystallization uniformity of the two, forming a firm columnar crystal, and improving the service life.
[0055] 3. Plasma sintering can effectively reduce the heating time, that is, the sintering time. The intermediate layer and the catalyst layer are coated and sintered layer by layer. Reducing the sintering time will greatly reduce the cracks caused by high-temperature sintering, reduce the substrate passivation caused by high-temperature sintering and cracks, and improve the overall performance.
[0056] 4. Existing plasma sintering has the advantages of fast heating rate and uniform temperature, but it requires connecting both ends of the anode to power and applying pulse current. Therefore, there are still many equipment problems to be overcome to achieve industrial production.
[0057] 5. The existing plasma sintering technology is mainly used for the preparation of bulk metal or ceramics. It mainly makes the temperature of the metal or ceramic powder quickly rise to close to the melting point, and under a certain pressure, it is dissolved into a bulk product. It is also used in material connection and gradient material preparation. It mainly uses pulse discharge heating and pressurization to form dense metal or ceramics. This process mainly uses the principle of fast plasma heating speed and does not require pressurization. Therefore, it is easier to implement in equipment design than traditional plasma sintering.
[0058] The present invention will be explained in detail below with reference to the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 Schematic diagram of the principle of plasma sintering in this application;
[0060] Figure 2 The metal substrate in this application is cut to size, the preparation of the substrate pretreatment intermediate layer and the activation layer, and the coating morphology of plasma sintering and resistance furnace sintering, wherein Figure (a) is a microscopic morphology of the sample surface prepared by plasma sintering, and Figure (b) is a microscopic morphology of the sample surface prepared by muffle furnace sintering;
[0061] Figure 3 The catalytic performance of different embodiments and comparative examples is compared, wherein Figure (a) shows the performance of the copper foil anode of embodiments 1-3 and comparative examples 1-5 in 0.5M sulfuric acid, and Figure (b) shows the performance of the electrolytic chlorine anode of embodiments 4-5 and comparative examples 7-10 in saturated sodium chloride. DETAILED DESCRIPTION
[0062] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0063] Example 1
[0064] This embodiment relates to a copper foil anode, and the preparation method thereof comprises the following steps:
[0065] (1) First, TA1 was selected as the metal substrate and the sample was cut to a size of 100*100 mm2 using a shearing machine;
[0066] (2) sandblasting the substrate obtained in step (1) using G18 steel sand at a pressure of 0.55 MPa to give the substrate a certain degree of roughness;
[0067] (3) placing the titanium substrate obtained in step (2) into a 20% hot hydrochloric acid solution and etching for 25 minutes;
[0068] (4) TaCl5 and TiCl4 are prepared in a ratio of 1:1 and dissolved in a hydrochloric acid solution to form a uniform liquid with a Ta5+ and Ti4+ concentration of 10 g / L each.
[0069] (5) The uniform solution obtained in step (4) is evenly applied to the titanium substrate obtained in step (3) using a roller brush, with a coating amount of 0.5 g / m 2 The coating amount will affect the thickness and density of the middle layer, and can ensure that the thickness of the middle layer is 0.1 to 1 μm.
[0070] (6) drying the titanium plate obtained in step (5) in air, placing it in a plasma sintering furnace, introducing air atmosphere, sintering it to 500° C., heating it for 5 min, and keeping it at this temperature for 10 min;
[0071] (7) Repeat steps (5) and (6) five times to obtain a semi-finished intermediate layer product;
[0072] (8) TaCl5 solution and H2IrCl6 solution were prepared in a hydrochloric acid solution in a ratio of 3:7 to prepare Ir 4+ The concentration of the mixed solution is 100g / L.
[0073] (9) The uniform solution obtained in step (8) is evenly applied to the titanium anode semi-finished product obtained in step (7) using a brush, and the weight gain of iridium per time is 2 g / cm 2 .
[0074] To ensure the final coating amount is 20g / m 2 The amount of a single coating should not be too large. First of all, on a certain area of the board, the more the coating, the more uneven it is; the smaller the amount of a single coating, the more coating times are required to ensure the final content, the longer the sintering time, resulting in overburning and affecting the service life of the substrate.
[0075] (10) The titanium plate obtained in step (9) is dried in air, placed in a plasma sintering furnace, introduced into an air atmosphere, sintered to 500° C., heated for 5 min, and kept warm for 10 min.
[0076] (11) Repeat steps 9 to 10 ten times until the Ir content reaches 20 g / cm 2 , and finally the anode product is obtained.
[0077] The anode provided in this embodiment is composed of a valve metal substrate, an intermediate layer and a metal activation layer. Figure 2 a shows the scanning electron microscope (SEM) image of the metal substrate after size cutting, preparation of substrate pretreatment intermediate layer and activation layer, and plasma sintering coating morphology. Figure 2 In a, it can be clearly seen that the coating is precipitated in a crystallized manner, and the crystals are pyramid-shaped columnar structures. This structure has a large specific surface area and strong stability.
[0078] Figure 2 b shows the SEM image of the metal substrate after size cutting, preparation of the substrate pretreatment intermediate layer and activation layer, and the morphology of the muffle furnace sintered coating. Figure 2 As can be seen in b, its crystal morphology is spike-like crystals. The impact resistance of this structure is weak and it is easy to break and fall off.
[0079] In order to verify the effects of different treatment processes on the electrochemical performance, polarization curve tests were performed on Examples 1-5 and Comparative Examples 1-10, respectively. Figure 3 a is the polarization curve test result of the copper foil anode prepared in Examples 1-3 and Comparative Examples 1-5, and the oxygen evolution potential level of the reaction samples is as follows: Figure 3 It can be seen from a that the potential of Example 1 is significantly lower, and the potential is lower during the production process, using less electricity.
[0080] Figure 3 b is the polarization curve test result of electrolytic chlorine prepared in Examples 4-5 and Comparative Examples 7-10. Figure 3 As can be seen from b, the potentials of Examples 4 and 5 are significantly lower, which indicates that the electrochemical performance of titanium anodes sintered by plasma in different fields is better.
[0081] It can be seen from the above chart that the sample sintered by plasma has columnar crystals, while the sample sintered by muffle furnace has needle-shaped crystals. The columnar crystals have better stability than the needle-shaped ones. The reason why the plasma sintering forms this morphology in the present invention is that the oxidation temperature range of iridium and tantalum is quite different, and the heating rate of plasma sintering is relatively fast, so that iridium and tantalum almost reach the oxidation temperature at the same time, improving the crystallization uniformity of each component, and reducing the overall sintering time, inhibiting the excessive growth of crystals, and inhibiting the segregation of crystals into dendrites, so that the crystals remain columnar crystals.
[0082] Example 2
[0083] This embodiment relates to a copper foil anode, and its preparation method is basically the same as that of Example 1, except that the metal salt solution in step (8) is changed to TaCl5 solution, H2IrCl6 solution and H2PtCl6 are mixed in a ratio of 3:4:3, and in step (11), the final iridium weight is 12 g / cm 2 , and finally the anode product is obtained.
[0084] Example 3
[0085] The present embodiment relates to a copper foil anode, and its preparation method is basically the same as that of the embodiment 1, except that the heating rate of steps (6) and (10) is reduced, and the heating time is prolonged, the heating time is 15 minutes, and the holding time is 10 minutes.
[0086] Example 4
[0087] This embodiment relates to an anode for electrolytic chlorine production, and its preparation method comprises the following steps:
[0088] (1) First, TA1 was selected as the metal substrate and the sample was cut to 100*100 mm using a shearing machine. 2 size;
[0089] (2) sandblasting the substrate obtained in step (1) using G18 steel sand at a pressure of 0.55 MPa to give the substrate a certain degree of roughness;
[0090] (3) placing the titanium substrate obtained in step (2) into a 20% hot hydrochloric acid solution and etching for 25 minutes;
[0091] (4) Prepare RuCl3 and TiCl4 in a 1:1 ratio and dissolve them in hydrochloric acid solution to prepare Ru 3+ and Ti 4+ All are uniform liquids at 10g / L.
[0092] (5) The uniform solution obtained in step (4) is evenly applied to the titanium substrate obtained in step (3) using a roller brush, with a coating amount of 0.25 g / m 2 ;
[0093] (6) drying the titanium plate obtained in step (5) in air, placing it in a plasma sintering furnace, introducing air atmosphere, sintering it to 500° C., heating it for 5 min, and keeping it at this temperature for 10 min;
[0094] (7) Repeat steps (5) and (6) four times to obtain a semi-finished intermediate layer product;
[0095] (8) Mix RuCl3 solution and H2IrCl6 solution in a ratio of 3:7 in hydrochloric acid solution to prepare Ru 3+ The concentration of the mixed solution is 10g / L.
[0096] (9) The uniform solution obtained in step (8) is evenly coated onto the titanium anode semi-finished product obtained in step (7) using a brush, and the weight gain of ruthenium per gram is 0.7 g / cm2.
[0097] (10) drying the titanium plate obtained in step (9) in air, placing it in a plasma sintering furnace, introducing air atmosphere, sintering to 500° C., heating for 5 min, and keeping the temperature for 10 min;
[0098] (11) Repeat steps 9 to 10 ten times until the Ru content reaches 7 g / cm 2 , and finally the anode product is obtained.
[0099] Example 5
[0100] This embodiment relates to an anode for electrolytic chlorine production, and its preparation method is basically the same as that of Example 4, except that the heating rate of steps (6) and (10) is reduced, the heating time is extended, the heating time is 15 minutes, and the insulation time is 10 minutes.
[0101] Comparative Example 1
[0102] This comparative example relates to a copper foil anode, and the preparation method is basically the same as that of Example 1, except that steps (4) to (7) are omitted, that is, the coated anode prepared in this comparative example has no intermediate layer structure.
[0103] Comparative Example 2
[0104] This comparative example relates to a copper foil anode, and its preparation method is basically the same as that of Example 1, except that the sintering equipment in step (6) and step (10) is a muffle furnace, the heating time is 30 minutes, and the insulation time is 10 minutes.
[0105] Comparative Example 3
[0106] This comparative example relates to a copper foil anode, the preparation method of which is basically the same as that of Example 1, except that the sintering equipment in step (6) and step (10) is a muffle furnace, the heating time is 30 minutes, the insulation time is 10 minutes, steps (4) to (7) are omitted, and there is no intermediate layer of titanium anode.
[0107] Comparative Example 4
[0108] This comparative example relates to a copper foil anode, and its preparation method is basically the same as that of Example 1, except that the sintering equipment in step (6) is a muffle furnace, the heating time is 30 minutes, and the heat preservation time is 10 minutes.
[0109] Comparative Example 5
[0110] This comparative example relates to a copper foil anode, and its preparation method is basically the same as that of Example 1, except that the sintering equipment in step (10) is a muffle furnace, the heating time is 30 minutes, and the heat preservation time is 10 minutes.
[0111] Comparative Example 6
[0112] This comparative example relates to an anode for electrolytic chlorine production, and the preparation method is basically the same as that of Example 4, except that steps (4) to (7) are omitted, that is, the coated anode prepared in this comparative example has no intermediate layer structure.
[0113] Comparative Example 7
[0114] This comparative example relates to an electrolytic chlorine anode, and the preparation method is basically the same as that of Example 4, except that the sintering equipment in step (6) and step (10) is a muffle furnace, the heating time is 30 minutes, and the insulation time is 10 minutes.
[0115] Comparative Example 8
[0116] This comparative example relates to an anode for electrolytic chlorine production, and the preparation method is basically the same as that of Example 4, except that the sintering equipment in step (6) and step (10) is a muffle furnace, the heating time is 30 minutes, the insulation time is 10 minutes, steps (4) to (7) are omitted, and there is no titanium anode with an intermediate layer.
[0117] Comparative Example 9
[0118] This comparative example relates to an anode for electrolytic chlorine production, and the preparation method is basically the same as that of Example 4, except that the sintering equipment in step (6) is a muffle furnace, the heating time is 30 minutes, and the insulation time is 10 minutes.
[0119] Comparative Example 10
[0120] This comparative example relates to an anode for electrolytic chlorine production, and the preparation method is basically the same as that of Example 4, except that the sintering equipment in step (10) is a muffle furnace, the heating time is 30 minutes, and the insulation time is 10 minutes.
[0121] Table 1 Performance comparison of embodiments and comparative examples
[0122]
[0123] The test conditions in Table 1 are as follows: life test in 20% sulfuric acid at a current density of 50 kA / m2, the temperature is kept constant at 50°C in a water bath, and the solution is circulated by a circulating pump at a flow rate of 0.5 m / s, and all samples are electrolyzed under the same environmental conditions; and 20 kA / m 2 The life test was carried out in 2M sodium chloride at a current density of 60°C in a water bath, and all samples were electrolyzed under the same environmental conditions.
[0124] Analyzing Table 1, within the range provided in this application, adjusting or changing the process parameters will not have a significant effect on the lifespan. The lifespan of the copper foil anode samples sintered in a muffle furnace is 43.1% shorter than that of the plasma sintered samples. The lifespan of the electrolytic chlorine anode samples sintered in a muffle furnace is 38.2% shorter than that of the plasma sintered samples. This is because the stability of the plasma sintered samples makes them more resistant to gas and water erosion. This result fully illustrates the advantages of plasma sintering.
[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
[0126] The above is an exemplary description of the present invention in combination with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as such non-substantial improvements are made by adopting the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A coated anode prepared by plasma sintering, characterized in that: It comprises a metal substrate and a metal activation layer coated on the surface of the substrate, and an oxide intermediate layer is provided between the substrate and the metal activation layer; The oxide intermediate layer is composed of at least one oxide of Ti, Ta, Nb, Pt, Pd, Rh, Ru, Ir, and Os; the metal activation layer is composed of at least one oxide of Ta, Pt, Pd, Rh, Ru, Ir, and Os; the oxide intermediate layer and the metal activation layer are both made by plasma sintering.
2. The coated anode prepared by plasma sintering according to claim 1, characterized in that: The oxide intermediate layer precursor solution is prepared by mixing the solutions containing components A1 and B1 uniformly and dissolving them in an organic solvent or hydrochloric acid; Among them, components A1 and B1 are at least one of Ti, Ta, Nb, Pt, Pd, Rh, Ru, Ir, and Os.
3. The coated anode prepared by plasma sintering according to claim 1 or 2, characterized in that: The thickness of the oxide intermediate layer is 0.1-1 μm.
4. The coated anode prepared by plasma sintering according to claim 1, characterized in that: The active metal layer precursor solution is prepared by mixing the solutions containing components A2 and B2 uniformly and dissolving them in an organic solvent or hydrochloric acid; The components A2 and B2 are at least one metal selected from Ta, Pt, Pd, Rh, Ru, Ir, and Os.
5. The coated anode prepared by plasma sintering according to claim 1, characterized in that: The thickness of the metal activation layer is 1-20 μm.
6. The coated anode prepared by plasma sintering according to claim 1, characterized in that: The substrate is a valve-type metal selected from titanium, tantalum or niobium, and forms a dense oxide film at an oxidation potential without dissolving; And / or, the valve-type metal is in the form of a plate, a mesh or a tube.
7. A method for preparing a coated anode prepared by plasma sintering, characterized in that: For preparing a coated anode prepared by plasma sintering as claimed in any one of claims 1 to 6, the preparation method comprises the following steps: (1) Surface roughness treatment: The cut substrate is subjected to sandblasting, shot blasting or magnetron sputtering to increase the surface roughness of the substrate; (2) Surface activation treatment: Use alkaline degreasing or acid washing to remove oxides on the surface of the substrate, and then dry it for later use; (3) preparing the intermediate layer, uniformly coating the oxide intermediate layer precursor solution on the surface of the substrate, cooling to room temperature after plasma sintering to obtain an oxide intermediate layer supported on the surface of the substrate, and obtaining a semi-finished product having an oxide intermediate layer; (4) Preparation of metal activation layer: The active metal layer precursor solution is evenly coated on the surface of the semi-finished product, and the metal activation layer is prepared by plasma sintering.
8. The method for preparing a coated anode prepared by plasma sintering according to claim 7, characterized in that: During the plasma sintering process of step (3) and step (4), oxygen or air is introduced to oxidize the metal salt.
9. The method for preparing a coated anode prepared by plasma sintering according to claim 7, characterized in that: Plasma sintering includes the following steps: Connect the two ends of the anode to the positive and negative electrodes of the plasma respectively, and start heating after power is turned on. The heating rate in the plasma sintering device is 80-120℃ / min, and the anode is heated from room temperature to 300℃-550℃; During the sintering process, excess air or oxygen atmosphere is introduced and the temperature is kept at normal pressure for 5 minutes to 20 minutes. After sintering, it is placed in the air to cool to room temperature.
10. An application of a coated anode prepared by plasma sintering, characterized in that: Application of the coated anode prepared by plasma sintering according to any one of claims 1 to 6 in the fields of copper foil production, electrolytic chlorine production, water treatment, seawater desalination, and printed circuit board manufacturing.
Citation Information
Cited By
Titanium-based composite oxide coating and method for producing the same
CN122669370A